EFEKTIVITAS PENDIDIKAN KESEHATAN DENGAN MEDIA VIDEO UNTUK MENINGKATKAN SIKAP DAN NIAT PENGGUNAAN AKDR - Dwi Kartikawati; Wahyu Pujiastuti; Masini Masini; Siti Rofi'ah (Midwifery Care Journal, 2020)
Family planning is an effort to create a quality of family by regulating the birth of children, the ideal distance and age of childbirth, and regulating pregnancy. One of the contraceptives that are less attractive to couples of childbearing age is the Alat Kontrasepsi Dalam Rahim (AKDR). Health education with video media can be done as an effort to increase the use of AKDR contraception. Theory of Planned Behavior states that a behavior begins with the formation of attitudes and intentions. This study used an quasi experimental study with non equivalent control group design on attitude variables and static group comparison on intention variables. Data analysis used paired t test on attitude and chi square on intention. The results of the study that health education with video media effectively increases attitudes in the used of AKDR with p value = 0.00 (p value 0.005) with video media more effective 4.75 higher than leaflet media, while health education with video media was not effective in increasing the intention to used an AKDR with p value = 0.269